α-Conotoxin MII-Sensitive Nicotinic Acetylcholine Receptors in the Nucleus Accumbens Shell Regulate Progressive Ratio Responding Maintained by Nicotine - Brunzell, Darlene H (Nature Publishing Group, 2010)
β2 subunit containing nicotinic acetylcholine receptors (β2(*)nAChRs; asterisk ((*)) denotes assembly with other subunits) are critical for nicotine self-administration and nicotine-associated dopamine (DA) release that supports nicotine reinforcement. The α6 subunit assembles with β2 on DA neurons where α6β2(*)nAChRs regulate nicotine-stimulated DA release at neuron terminals. Using local infusion of α-conotoxin MII (α-CTX MII), an antagonist with selectivity for α6β2(*)nAChRs, the purpose of these experiments was to determine if α6β2(*)nAChRs in the nucleus accumbens (NAc) shell are required for motivation to self-administer nicotine. Long-Evans rats lever-pressed for 0.03 mg/kg, i.v., nicotine accompanied by light+tone cues (NIC) or for light+tone cues unaccompanied by nicotine (CUEonly). Following extensive training, animals were tested under a progressive ratio (PR) schedule that required an increasing number of lever presses for each nicotine infusion and/or cue delivery. Immediately before each PR session, rats received microinfusions of α-CTX MII (0, 1, 5, or 10 pmol per side) into the NAc shell or the overlying anterior cingulate cortex. α-CTX MII dose dependently decreased break points and number of infusions earned by NIC rats following infusion into the NAc shell but not the anterior cingulate cortex. Concentrations of α-CTX MII that were capable of attenuating nicotine self-administration did not disrupt locomotor activity. There was no effect of infusion on lever pressing in CUEonly animals and NAc infusion α-CTX MII did not affect locomotor activity in an open field. These data suggest that α6β2(*)nAChRs in the NAc shell regulate motivational aspects of nicotine reinforcement but not nicotine-associated locomotor activation.